Peningkatan Laju Disolusi Ketoprofen Dengan Teknik Co-Grinding Menggunakan Polimer Hydroxypropyl Methylcellulose E6 - Najmi Hilaliyati; Elfi Sahlan Ben; Erizal Zaini (Fakultas Farmasi Universitas Andalas, 2017)
Improvement of the dissolution rate of ketoprofen as a model for a poorly water-soluble drug by solid state co-grinding technique with hydrophilic polymer hydroxypropyl methylcellulose E6 (HPMC) using mortar grinder apparatus have been investigated. Three different formulations prepared with varying drug : carrier ratio 1:2, 1:1, and 2:1 (w/w). Physical mixture prepared with ratio 1:1 (w/w). X-ray diffraction showed decrease of peak intensity of ketoprofen. DSC analysis showed decrease of melting point of ketoprofen. FTIR analysis showed no chemical interaction between drug and polymer. In this investigation, it was found that solubility tended to increase with increase in the amount of polymer used. Solid dispersion ratio 1:2 showed the highest solubility (6,5 fold). However, unlike the solubility results, the dissolution rate increased with decreases in polymer concentration due to thick diffusion layer formation of the polymer. Solid dispersion ratio 2:1 showed the highest dissolution (2,1 fold).